2013
DOI: 10.1161/jaha.113.000150
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of HCN Channels in the Ventricular Myocardium Contributes to Enhanced Arrhythmicity in Mouse Failing Hearts

Abstract: BackgroundThe efficacy of pharmacological interventions to prevent sudden arrhythmic death in patients with chronic heart failure remains limited. Evidence now suggests increased ventricular expression of hyperpolarization‐activated cation (HCN) channels in hypertrophied and failing hearts contributes to their arrythmicity. Still, the role of induced HCN channel expression in the enhanced arrhythmicity associated with heart failure and the capacity of HCN channel blockade to prevent lethal arrhythmias remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 44 publications
6
70
0
Order By: Relevance
“…In their study, ivabradine reduced lethal arrhythmias associated with dilated cardiomyopathy in mice, and beta-adrenergic stimulation conversely increased arrhythmogenecity [21]. Also, another study showed that I f current activity increases the pro-arrhythmogenic potential in the failing myocytes through prolongation of the repolarisation phase in ventricular action potentials [22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In their study, ivabradine reduced lethal arrhythmias associated with dilated cardiomyopathy in mice, and beta-adrenergic stimulation conversely increased arrhythmogenecity [21]. Also, another study showed that I f current activity increases the pro-arrhythmogenic potential in the failing myocytes through prolongation of the repolarisation phase in ventricular action potentials [22].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Kuwabara et al [21] examined the effect of ivabradine on survival and arrhythmicity in transgenic mice, which is a useful mouse model of dilated cardiomyopathy leading to sudden death. In their study, ivabradine reduced lethal arrhythmias associated with dilated cardiomyopathy in mice, and beta-adrenergic stimulation conversely increased arrhythmogenecity [21].…”
Section: Discussionmentioning
confidence: 99%
“…We also carried out a preliminary analysis of transgenic mice overexpressing HCN2 in their hearts (HCN2-Tg) and reported that they were vulnerable to β-adrenergic-induced abnormal electrical activity [10]. In the present study, we carried out a detailed analysis of the electrocardiographic and electrophysiological properties of single ventricular myocytes from HCN2-Tg mice.…”
Section: Introductionmentioning
confidence: 91%
“…We overexpressed mouse HCN2 cDNA in the hearts of C57BL/6 mice using the α-MHC promoter (HCN2-Tg) [10]. HCN2-Tg and their wildtype (WT) littermates were used while they were between 10 and 14 weeks of age.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…26 The heart rates of dnNRSF-Tg mice are slower than those of wild-type mice. Moreover, at a dose of 7 mg · kg -1 · day -1 , ivabradine signifi- .…”
Section: Hcn Channelsmentioning
confidence: 99%